NAADP, a new intracellular messenger that mobilizes Ca2+ from acidic stores. - Galione, A (2006)
NAADP (nicotinic acid-adenine dinucleotide phosphate) is a recently described Ca2+-mobilizing molecule. First characterized in the sea urchin egg, it has been shown to mobilize Ca2+ from intracellular stores in a wide range of cells from different organisms. It is a remarkably potent molecule, and recent reports show that its cellular levels change in response to a variety of agonists, confirming its role as a Ca2+-mobilizing messenger. In many cases, NAADP appears to interact with other Ca2+-mobilizing messengers such as IP3 (inositol 1,4,5-trisphosphate) and cADP-ribose in shaping cytosolic Ca2+ signals. What is not clear is the molecular nature of the NAADP-sensitive Ca2+ release mechanism and its subcellular localization. This review focuses on the recent progress made in sea urchin eggs, which indicates that NAADP activates a novel Ca2+ release channel distinct from the relatively well-characterized IP3 and ryanodine receptors. Furthermore, in the sea urchin egg, the NAADP-sensitive store appears to be separate from the endoplasmic reticulum and is most likely an acidic store. These findings have also been reinforced by similar findings in mammalian cells, and a unified model for NAADP-induced Ca2+ signalling is presented.